CoS nanoflower composite for negative electrode of lithium ion battery and preparation method thereof
Patent Information
- Application Number
- CN202610900214.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-22
- Publication Date
- 2026-09-15
Smart Images

Figure CN122762631A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium battery electrode materials technology, specifically to a CoS nanoflower composite material for lithium-ion battery anodes and its preparation method. Background Technology
[0002] Lithium-ion batteries serve as energy storage carriers for portable electronic devices and electric vehicles; therefore, the key to improving lithium battery performance lies in the development of high-performance anode materials. Currently used metal oxide anode materials suffer from technical problems such as poor electronic conductivity and low material utilization, severely limiting their capacity under high-power charge-discharge scenarios. While transition metal sulfides possess higher theoretical capacity and conductivity, they are prone to drastic volume deformation during cycling, leading to structural collapse and making it difficult to meet usage requirements in terms of cycle and rate performance. Furthermore, a single electrode material cannot simultaneously possess high capacity, high conductivity, and structural stability, and conventional substrate materials also struggle to synergistically address the technical challenges of active material loading and structural buffering. Summary of the Invention
[0003] The purpose of this invention is to provide a Co3O4@CoS@CC composite material with a large specific surface area, high conductivity network, enhanced structural stability and excellent electrochemical energy storage performance.
[0004] The technical solution of the present invention:
[0005] A CoS nanoflower composite material for lithium-ion battery anodes, wherein the composite material is Co3O4@CoS@CC, the composite material uses flexible carbon cloth as a conductive substrate, and a Co3O4 nanowire array is grown in situ on the surface of the flexible carbon cloth; a CoS nanoflower structure is uniformly coated on the outer surface of the Co3O4 nanowire array, and the CoS nanoflower structure is composed of interconnected CoS nanosheets.
[0006] Preferably, the average length of the nanowires in the Co3O4 nanowire array is 3.3 μm, and the average size of the nanowire tips is 0.5 μm; the average size of the CoS nanosheets in the CoS nanoflower structure is 20 nm.
[0007] A method for preparing CoS nanoflower composite materials for lithium-ion battery anodes includes the following steps:
[0008] S1 dissolves cobalt nitrate hexahydrate, ammonium fluoride, and urea in deionized water and stirs at room temperature for 30 minutes to obtain a precursor solution;
[0009] S2 The precursor solution is transferred to a polytetrafluoroethylene-lined reactor with built-in flexible carbon cloth, and a hydrothermal reaction is carried out at 120°C for 5 hours.
[0010] After the S3 hydrothermal reaction is completed, the mixture is cooled to room temperature, the flexible carbon cloth is removed, rinsed repeatedly with deionized water, and dried at 60°C for 3 hours to obtain the precursor.
[0011] S4 The dried precursor is placed in a nitrogen environment at 5℃·min -1 The temperature was increased to 350℃ and held for 2 hours to obtain Co3O4@CC intermediate loaded with Co3O4 nanowire array;
[0012] S5 uses the Co3O4@CC intermediate as the working electrode, a platinum sheet as the counter electrode, and an Ag / AgCl electrode as the reference electrode to construct a three-electrode system. Electrodeposition is performed in the electrolyte using cyclic voltammetry to deposit CoS on the surface of the Co3O4 nanowire array.
[0013] After S6 electrodeposition is completed, the electrodeposition product is removed and rinsed repeatedly with ethanol and deionized water in sequence.
[0014] S7 placed the rinsed sample in a vacuum drying oven at 60℃ and dried it for 3 hours to obtain the Co3O4@CoS@CC composite material.
[0015] Preferably, in step S1, the amounts of cobalt nitrate hexahydrate, ammonium fluoride, and urea are 0.582g, 0.444g, and 1.2g, respectively, and the amount of deionized water is 40mL.
[0016] Preferably, in step S5, the electrolyte is a mixed aqueous solution of 0.05 mol / L cobalt chloride hexahydrate and 1.0 mol / L thiourea.
[0017] Preferably, in step S5, the cyclic voltammetric electrodeposition requires setting the potential range to -1.2V to 0.2V and the scan rate to 10mV·s. -1 The cycle is repeated 4 times.
[0018] An application of a CoS nanoflower composite material, wherein the composite material Co3O4@CoS@CC can be used to prepare lithium-ion battery anodes.
[0019] A lithium-ion battery, wherein the negative electrode of the lithium-ion battery comprises the Co3O4@CoS@CC composite material as described in claim 1 or 2.
[0020] The beneficial effects of this invention are as follows:
[0021] The composite material of this invention can form a highly efficient conductive network and a large specific surface area, which can improve structural stability and electrochemical energy storage performance. Moreover, the material itself has abundant redox sites and excellent electronic conductivity, which can effectively accelerate ion and electron transport and alleviate volume expansion during charging and discharging. This gives the material good flexibility, high capacity and excellent cycle stability, making it a promising candidate for lithium-ion batteries.
[0022] The above description is merely an overview of the technical solution of the present invention. In order to better understand the technical means of the present invention and to implement it in accordance with the contents of the specification, the preferred embodiments of the present invention are described in detail below with reference to the accompanying drawings. Attached Figure Description
[0023] Figure 1 This is a schematic diagram of the preparation process of Co3O4@CC and Co3O4@CoS@CC;
[0024] Figure 2 In the middle (a1-a2), the field emission scanning electron microscope (FEM) and energy dispersive spectroscopy (EDS) micrographs of Co3O4@CC are shown; (b1-b2) show the field emission scanning electron microscope (FEM) and EDS micrographs of Co3O4@CoS@CC are shown.
[0025] Figure 3 (a–b) are field emission scanning electron microscope images of Co3O4@CoS@CC; (c–h) are energy dispersive spectral elemental distribution maps of Co3O4@CoS@CC.
[0026] Figure 4 (a) X-ray diffraction patterns of Co3O4@CC and Co3O4@CoS@CC; (b) Raman spectra of Co3O4@CC and Co3O4@CoS@CC.
[0027] Figure 5 The diagram shows the X-ray photoelectron spectra of Co3O4@CoS@CC, where (a) is the full spectrum of Co3O4@CoS@CC; (b) is the 1s spectrum of carbon; (c) is the 1s spectrum of oxygen; (d) is the 2p spectrum of cobalt; and (e) is the 2p spectrum of sulfur.
[0028] Figure 6 The diagram shows the electrochemical performance of Co3O4@CC and Co3O4@CoS@CC, where (a) is the cyclic voltammetry curve of Co3O4@CoS@CC; (b–c) are the cyclic voltammetry curves of Co3O4@CC and Co3O4@CoS@CC at 100 mAg. -1 Charge-discharge voltage curves at current density; (d) shows the charge-discharge voltage curves of Co3O4@CC and Co3O4@CoS@CC at 100 mAg. -1(e) shows the cycling performance of Co3O4@CC and Co3O4@CoS@CC at different current densities; (f) shows the Nyquist plots of Co3O4@CC and Co3O4@CoS@CC after 100 cycles. Detailed Implementation
[0029] The technical solution of the present invention will now be clearly and completely described with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Example
[0030] like Figure 1 As shown, the preparation process of a CoS nanoflower composite material for lithium-ion battery anodes is as follows:
[0031] S1: Using hydrophilic flexible carbon cloth (CC) as a substrate, weigh 0.582g of cobalt nitrate hexahydrate (Co(NO3)2·6H2O), 0.444g of ammonium fluoride (NH4F) and 1.2g of urea (CO(NH2)2), and dissolve them in 40mL of deionized water. Then stir at room temperature for 30 minutes to obtain a homogeneous precursor solution.
[0032] S2: The precursor solution was placed in a 50ml polytetrafluoroethylene-lined reactor, and flexible carbon cloth (CC) was added. The reactor was kept at 120℃ for hydrothermal reaction for 5 hours. After the reaction was completed, the reactor was allowed to cool naturally to room temperature. The flexible carbon cloth (CC) was then removed, rinsed repeatedly with deionized water, and dried in an oven at 60℃ for 3 hours to obtain the precursor.
[0033] S3: The dried precursor is placed in a nitrogen atmosphere at 5℃·min -1 The temperature was increased to 350℃ and held for 2 hours to obtain the Co3O4@CC intermediate. This cobalt tetroxide (Co3O4) nanowire array was uniformly grown on the surface of flexible carbon cloth (CC), with an average nanowire length of 3.3 μm and an average tip size of 0.5 μm.
[0034] S4: Co3O4@CoS@CC composite materials were prepared by three-electrode electrodeposition, using Co3O4@CC as the working electrode, a platinum sheet as the counter electrode, and a silver / silver chloride (Ag / AgCl) electrode as the reference electrode, and immersed in an electrolyte. The electrolyte consisted of a mixed aqueous solution of 0.05 mol / L cobalt chloride hexahydrate (CoCl2·6H2O) and 1.0 mol / L thiourea (H2NSNH2). Electrodeposition was performed using cyclic voltammetry, with the potential range set from -1.2 V to 0.2 V and the scan rate at 10 mV·s. -1The cycle is repeated 4 times.
[0035] S5: During electrodeposition, cobalt sulfide (CoS) nanoflower structures uniformly coat the outer surface of the cobalt tetroxide (Co3O4) nanowire array. The nanoflowers are composed of interconnected cobalt sulfide (CoS) nanosheets with an average size of 20 nm. After electrodeposition, the sample is removed and repeatedly rinsed with ethanol and deionized water, and finally dried in a 60°C vacuum drying oven for 3 hours to obtain the final Co3O4@CoS@CC composite material.
[0036] Experimental test:
[0037] The performance test in this experiment used the Co3O4@CoS@CC composite material as the test target and the Co3O4@CC intermediate as the control.
[0038] like Figure 2 As shown, the microstructure of the Co3O4@CC intermediate and the Co3O4@CoS@CC composite material was characterized. Figure 2 As shown in a1 to a2, a1 is a field emission scanning electron microscope (SEM) image of Co3O4@CC, and a2 is an energy dispersive spectroscopy (EDS) spectrum of Co3O4@CC. The SEM images show that the Co3O4@CC composite material is composed of a large number of uniformly sized and morphologically consistent nanowire arrays with an average length of 3.3 μm and an average tip size of 0.5 μm. EDS analysis indicates that it is mainly composed of cobalt (Co), oxygen (O), and carbon (C). Figure 2 As shown in b1 to b2, b1 is a field emission scanning electron microscope image of Co3O4@CoS@CC, and b2 is an energy dispersive spectroscopy (EDS) spectrum of Co3O4@CoS@CC, indicating that Co3O4@CoS@CC is composed of cobalt (Co), oxygen (O), carbon (C) and sulfur (S).
[0039] like Figure 3 As shown, in the Co3O4@CoS@CC composite material, cobalt tetroxide (Co3O4) nanowires are completely coated with fine cobalt sulfide (CoS) nanoflowers. These nanoflowers consist of numerous nanosheets with an average size of 20 nm. This unique structure of the Co3O4@CoS@CC composite material is beneficial for improving electrochemical performance: increasing the contact area provides more active sites, and the shorter ion diffusion path accelerates ion transport in the electrolyte. Figure 3 The scanning electron microscope images further confirmed that the nanoflower structure was uniformly coated on the surface of the nanowires. Figure 3 Energy dispersive spectroscopy (EDS) analysis from c to h showed that the four elements cobalt (Co), oxygen (O), carbon (C), and sulfur (S) were evenly distributed, with sulfur (S) mainly concentrated on the surface of the composite material, proving that cobalt sulfide (CoS) was successfully deposited on the surface of cobalt tetroxide (Co3O4).
[0040] Structural characterization results as follows Figure 4 As shown. Figure 4 In the X-ray diffraction pattern of Co3O4@CC, five diffraction peaks appear at 31.3°, 36.8°, 44.8°, 59.4°, and 65.2°, corresponding to the 220, 311, 400, 511, and 440 crystal planes of cobalt tetroxide (Co3O4), respectively. After electrodepositing CoS particles on Co3O4@CC, the above five diffraction peaks shifted overall, mainly due to the presence of sulfur ions (S). 2- Entering the cobalt tetroxide (Co3O4) lattice or changing the valence state / coordination environment of cobalt ions, interdiffusion generates tensile stress, due to S 2- Radius greater than O 2- As the lattice constant increases, the lattice expands, indicating the presence of CoS and suggesting that Co3O4 and CoS form a well-structured heterojunction interface. Figure 4 In the Raman spectrum of b, the Co3O4@CC sample at 182, 464, 505, and 666 cm⁻¹ -1 The characteristic peak of cobalt tetroxide (Co3O4) appears at 321, 399 and 601 cm⁻¹; the intensity of the characteristic peak of cobalt tetroxide (Co3O4) decreases in the Co3O4@CoS@CC sample, while the intensity of the characteristic peak of cobalt tetroxide (Co3O4) decreases at 321, 399 and 601 cm⁻¹. -1 The appearance of a new characteristic peak belonging to cobalt sulfide (CoS) confirms the presence of a dense cobalt sulfide (CoS) layer. The D / G band of the flexible carbon cloth (CC) was not observed in the Raman spectrum, indirectly indicating that cobalt sulfide (CoS) is uniformly and completely coated on the surface of the flexible carbon cloth (CC).
[0041] like Figure 5 As shown, Figure 5 A proves that the composite material contains cobalt (Co), oxygen (O), carbon (C), and sulfur (S). Figure 5 The carbon 1s spectrum of b shows three peaks at 284.80, 286.05, and 289.19 eV, corresponding to carbon-carbon bond (CC), carbon-oxygen single bond (CO), and carbon-oxygen double bond (C=O), respectively. Figure 5 The oxygen 1s spectrum of c shows three peaks at 530.36, 531.29, and 532.69 eV, corresponding to lattice oxygen, oxygen vacancy, and adsorbed oxygen, respectively. Figure 5 The cobalt 2p spectrum of d shows two main peaks at 781.18 and 797.04 eV, two secondary peaks at 779.79 and 795.65 eV, and two satellite peaks at 785.26 and 802.06 eV, corresponding to cobalt 2p, respectively. 3 / 2 Cobalt 2p 1 / 2 The energy difference is approximately 15.9 eV, proving that cobalt exists in a divalent state (Co). 2+ ) and trivalent (Co 3+ It exists in the form of ). Figure 5In the sulfur 2p spectrum of e, the peaks at 163.29 and 164.92 eV correspond to carbon-sulfur bonds (CS), and the peaks at 166.54 and 167.44 eV correspond to sulfite ions (SO3). 2- The peaks at 168.50 and 169.85 eV correspond to sulfate (SO4) ions. 2- The above results confirm the coexistence of cobalt tetroxide (Co3O4) and cobalt sulfide (CoS) in the composite material.
[0042] like Figure 6 As shown, Figure 6 a demonstrates the 2p3 / 2@CoS@CC electrode at 0.1 mV·s -1 Cyclic voltammetry curves for the first three scans at the scan rate. In the initial cathode scan, the reduction peak at 0.82 V corresponds to the reduction reaction of cobalt sulfide (CoS), specifically:
[0043]
[0044] The reduction peak at 0.43 V corresponds to the formation of the solid electrolyte interfacial film and electrolyte decomposition. During anodic oxidation, the specific reactions are as follows:
[0045] .
[0046] The second oxidation peak shifts to 1.12V, and the reduction peaks shift to 0.58V and 1.72V, respectively, due to improved electrode reaction kinetics.
[0047] Therefore, the overall reversible reaction equation for the entire electrode process can be expressed as follows:
[0048] .
[0049] The high overlap between the second and third cyclic voltammetry curves indicates that the electrode has good reversibility.
[0050] like Figure 6 As shown in b and 6c, at 100mAg -1 At the specified current density, the initial charge specific capacity of Co3O4@CoS@CC is 1266.88 mAh g. -1 The initial discharge specific capacity was 1273.38 mAh g. -1 All are higher than the 1003.78 mAh g of Co3O4@CC. -1 and 1008.4mAhg -1 As the number of cycles increases, the charge-discharge curves almost overlap, demonstrating the good reversibility of Co3O4@CoS@CC.
[0051] Figure 6Cyclic performance tests at d show that Co3O4@CoS@CC performs well at 100 mAg. -1 The initial discharge specific capacity was 1273.11 mAh g. -1 The capacity exhibits an activation phenomenon of initial decrease, followed by an increase and then a further decrease with cycling. The initial decrease is due to the reduction and decomposition of the electrolyte on the electrode surface, forming a solid electrolyte interfacial film, which consumes some electrolyte and lithium ions. Simultaneously, irreversible side reactions occur in a small amount of unreacted residual impurities or metastable phases on the electrode surface, leading to a temporary capacity loss. The subsequent increase occurs as the electrolyte gradually penetrates into the electrode interior, allowing cobalt tetroxide (Co3O4) and cobalt sulfide (CoS) to gradually participate in the reaction. At the same time, in the early stages of cycling, cobalt sulfide (CoS) undergoes lattice changes or phase transitions, exposing more electrochemically active sites, thus gradually increasing the capacity. The final decrease is due to the weakening interfacial bonding of the core-shell structure caused by long-term cycling, leading to the pulverization and detachment of the cobalt sulfide (CoS) layer. This results in a sharp increase in the contact resistance between the carbon cloth substrate and the active material, further exacerbating capacity decay. After 200 cycles, the capacity remains at 677.3 mAh g⁻¹. -1 The reversible capacity of Co3O4@CC is 99.73%; while the capacity of Co3O4@CC after 200 cycles is only 230.96 mAhg. -1 .
[0052] like Figure 6 As shown in e, Co3O4@CoS@CC at 100, 200, 300 and 500 mAg -1 The average discharge specific capacities at the given current densities were 1220.7, 964.42, 815.62, and 639.02 mAh g, respectively. -1 Co3O4@CC at 100, 200, 300 and 500 mAg -1 The average discharge specific capacities at the specified current densities were 942.76, 714.23, 607.50, and 491.38 mAh g, respectively. -1 When the current density recovers to 100 mAg -1 The capacity of Co3O4@CoS@CC can be stably maintained at 961.86mAh g. -1 The results show that it is significantly better than Co3O4@CC, proving that the introduction of CoS can increase the specific surface area and the number of active sites, giving the composite material good cycle stability and performance.
[0053] like Figure 6 As shown in f, Figure 6f represents the Nyquist plot and equivalent circuit of the two electrodes. The sloping straight line in the low-frequency region is controlled by lithium-ion diffusion, while the compressed semicircle in the high-frequency region is dominated by charge transfer resistance. Rs, Rsei, and Rct represent contact resistance, film resistance, and charge transfer resistance, respectively. The Co3O4@CoS@CC electrode has a contact resistance Rs of 38.54 Ω, a film resistance Rsei of 56.68 Ω, and a charge transfer resistance Rct of 104 Ω; while the Co3O4@CC electrode has a contact resistance Rs of 21.92 Ω, a film resistance Rsei of 259.8 Ω, and a charge transfer resistance Rct of 2250 Ω. The comparison shows that the Co3O4@CoS@CC electrode has lower film resistance Rsei and charge transfer resistance Rct, with the charge transfer resistance Rct decreasing significantly from 2250 Ω to 104 Ω. This is because the cobalt sulfide (CoS) shell optimizes the electron transport path. Meanwhile, the Co3O4@CoS@CC exhibits a steeper gradient in the low-frequency region, demonstrating a faster diffusion rate of lithium ions in this composite electrode. This proves that the faster diffusion rate of electrolyte ions within the composite electrode results in better electrochemical performance, and that the lower charge transfer resistance and higher ion diffusion rate contribute to the high specific capacity of Co3O4@CoS@CC.
[0054] In summary
[0055] This invention employs a simple hydrothermal method combined with electrodeposition to prepare Co3O4@CoS@CC composite materials. The cobalt sulfide nanoflower structure effectively increases the specific surface area of the material, improves its electrical conductivity, promotes lithium-ion diffusion, and significantly alleviates volume expansion during charge and discharge.
[0056] When used as a negative electrode material in lithium-ion batteries, this composite material exhibits performance at 100 mAg. -1 After cycling 200 times at a current density, it still maintains 677.3 mAh g. -1 The high reversible capacity is far superior to the 230.96 mAh g of the Co3O4@CC electrode under the same conditions. -1 The uniformly distributed cobalt sulfide (CoS) nanosheets not only improve the overall conductivity and electrolyte penetration efficiency, but also effectively buffer volume expansion during cycling. Furthermore, the prepared Co3O4@CoS@CC composite material exhibits flexibility, high capacity, and excellent cycle stability, showing great potential for large-scale applications in lithium-ion batteries.
[0057] The embodiments described above are merely illustrative of implementation methods of the present invention, and while the descriptions are specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.
Claims
1. A CoS nanoflower composite material for lithium-ion battery anodes, characterized in that, The composite material is Co3O4@CoS@CC, with flexible carbon cloth as the conductive substrate. Co3O4 nanowire arrays are grown in situ on the surface of the flexible carbon cloth. CoS nanoflower structures are uniformly coated on the outer surface of the Co3O4 nanowire arrays. The CoS nanoflower structures are composed of interconnected CoS nanosheets.
2. The cobalt sulfide nanoflower composite material according to claim 1, characterized in that, The average length of the nanowires in the Co3O4 nanowire array is 3.3 μm, and the average size of the nanowire tips is 0.5 μm; the average size of the CoS nanosheets in the CoS nanoflower structure is 20 nm.
3. A method for preparing CoS nanoflower composite materials for lithium-ion battery anodes, characterized in that, Includes the following steps: S1 dissolves cobalt nitrate hexahydrate, ammonium fluoride, and urea in deionized water and stirs at room temperature for 30 minutes to obtain a precursor solution; S2 The precursor solution is transferred to a polytetrafluoroethylene-lined reactor with built-in flexible carbon cloth, and a hydrothermal reaction is carried out at 120°C for 5 hours. After the S3 hydrothermal reaction is completed, the mixture is cooled to room temperature, the flexible carbon cloth is removed, rinsed repeatedly with deionized water, and dried at 60°C for 3 hours to obtain the precursor. S4 The dried precursor is placed in a nitrogen environment at 5℃·min -1 The temperature was increased to 350℃ and held for 2 hours to obtain Co3O4@CC intermediate loaded with Co3O4 nanowire array; S5 uses the Co3O4@CC intermediate as the working electrode, a platinum sheet as the counter electrode, and an Ag / AgCl electrode as the reference electrode to construct a three-electrode system. Electrodeposition is performed in the electrolyte using cyclic voltammetry to deposit CoS on the surface of the Co3O4 nanowire array. After S6 electrodeposition is completed, the electrodeposition product is removed and rinsed repeatedly with ethanol and deionized water in sequence. S7 placed the rinsed sample in a vacuum drying oven at 60℃ and dried it for 3 hours to obtain the Co3O4@CoS@CC composite material.
4. The method for preparing CoS nanoflower composite material for lithium-ion battery anodes according to claim 3, characterized in that, In step S1, the amounts of cobalt nitrate hexahydrate, ammonium fluoride, and urea used are 0.582g, 0.444g, and 1.2g, respectively, and the amount of deionized water used is 40mL.
5. The method for preparing CoS nanoflower composite material for lithium-ion battery anode according to claim 3, characterized in that, In step S5, the electrolyte is a mixed aqueous solution of 0.05 mol / L cobalt chloride hexahydrate and 1.0 mol / L thiourea.
6. The method for preparing CoS nanoflower composite material for lithium-ion battery anode according to claim 5, characterized in that, In step S5, the cyclic voltammetric electrodeposition requires setting the potential range to -1.2V to 0.2V and the scan rate to 10mV·s. -1 The cycle is repeated 4 times.
7. The application of the CoS nanoflower composite material as described in claim 1 or 2, characterized in that, The composite material Co3O4@CoS@CC can be used to prepare lithium-ion battery anodes.
8. A lithium-ion battery, characterized in that, The negative electrode of the lithium-ion battery comprises the Co3O4@CoS@CC composite material as described in claim 1 or 2.